2015
DOI: 10.1016/j.bbi.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative meta-analysis of interleukins 6 and 1β, tumour necrosis factor α and C-reactive protein in patients with major depressive disorder

Abstract: HighlightsThis meta-analysis confirms a robust link between IL-6, CRP and major depression.The role of TNF-α and IL-1β in major depression remains uncertain.Further mechanistic and immunotherapeutic studies on IL-6 and CRP are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
584
12
18

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 949 publications
(658 citation statements)
references
References 95 publications
44
584
12
18
Order By: Relevance
“…Indeed, over the past several decades, data demonstrating increased innate immune responses and inflammation in patients with major depression have dominated the literature . For example, a multitude of studies have described increases in inflammatory cytokines in the peripheral blood and cerebrospinal fluid (CSF) of depressed patients (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015). In addition, numerous studies have documented increases in peripheral blood acute-phase reactants, chemokines, and adhesion molecules (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, over the past several decades, data demonstrating increased innate immune responses and inflammation in patients with major depression have dominated the literature . For example, a multitude of studies have described increases in inflammatory cytokines in the peripheral blood and cerebrospinal fluid (CSF) of depressed patients (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015). In addition, numerous studies have documented increases in peripheral blood acute-phase reactants, chemokines, and adhesion molecules (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
“…In addition, numerous studies have documented increases in peripheral blood acute-phase reactants, chemokines, and adhesion molecules (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015). In several meta-analyses of this literature, the most well-documented and reproducible findings have included increases in peripheral blood concentrations of the cytokines interleukin-6 (IL-6) and tumor necrosis factor (TNF) and the acute-phase reactant C-reactive protein (CRP) (Howren et al, 2009;Dowlati et al, 2010;Haapakoski et al, 2015). In addition to increases in inflammatory markers in depressed subjects, a number of polymorphisms in genes associated with inflammation, including IL-1β, IL-6, and TNF, as well as CRP, have been linked to the development of mood and anxiety disorders as well as treatment response (Bufalino et al, 2012;Michopoulos et al, 2015).…”
Section: Foundations For the Hypothesis That The Immune System Plays mentioning
confidence: 99%
See 1 more Smart Citation
“…In mood disorders, several studies have suggested that the chronic mild inflammation indicated by elevated C-reactive protein (Courtet et al, 2015;Rapaport et al, 2015;Uher et al, 2014) as well as the quantification of the levels of inflammatory cytokines such as IL-6, IL-10 and TNF (de Witte et al, 2014;Ducasse et al, 2015b;Haapakoski et al, 2015;Halaris et al, 2015;Rethorst et al, 2013) could prove to be useful biomarkers for improved diagnosis and the detection of treatment refractoriness (Strawbridge et al, 2015), as well as indicators of the risk of suicide. As an increasing number of inflammatory factors are tested, an emerging picture supports the idea that a complex network of cytokines is involved in the pathophysiology of disease such as major depression (Dahl et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analyses showed higher blood levels of proinflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin 6 (IL-6), in drugfree depressed patients compared with healthy controls (10)(11)(12)(13). Studies using postmortem brain samples showed elevated gene expression of proinflammatory cytokines in the frontal cortex of people with a history of depression (14,15).…”
mentioning
confidence: 99%